2024
DOI: 10.1021/acs.analchem.3c04430
|View full text |Cite
|
Sign up to set email alerts
|

Probing Molecular Packing of Lipid Nanoparticles from 31P Solution and Solid-State NMR

Ryan Schroder,
Phillip J. Dorsey,
Joe Vanderburgh
et al.

Abstract: Lipid nanoparticles (LNPs) are intricate multicomponent systems widely recognized for their efficient delivery of oligonucleotide cargo to host cells. Gaining insights into the molecular properties of LNPs is crucial for their effective design and characterization. However, analysis of their internal structure at the molecular level presents a significant challenge. This study introduces 31 P nuclear magnetic resonance (NMR) methods to acquire structural and dynamic information about the phospholipid envelope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…S12†), revealing solely distinctive peaks corresponding to P–N. 52 Based on this inference, in the Cu–C 3 N 4 -HA, non-metallic elements substitute for C in the matrix, forming X–N coordination. Based on the aforementioned inference, it could be confirmed that in the constructed Cu–C 3 N 4 -HA, non-metallic elements substitute for C in the matrix, forming HA-N coordination.…”
Section: Resultsmentioning
confidence: 92%
“…S12†), revealing solely distinctive peaks corresponding to P–N. 52 Based on this inference, in the Cu–C 3 N 4 -HA, non-metallic elements substitute for C in the matrix, forming X–N coordination. Based on the aforementioned inference, it could be confirmed that in the constructed Cu–C 3 N 4 -HA, non-metallic elements substitute for C in the matrix, forming HA-N coordination.…”
Section: Resultsmentioning
confidence: 92%
“…In recent years, these tools have significantly advanced our understanding by pushing the boundaries in various areas. Examples include molecular or atomic level elucidation of key structures and interactions in amorphous solid dispersions within solid dosages, critical (de)stabilizing interactions in parenteral peptide or protein formulations, microenvironmental properties in lyophilized , and frozen biologics, and the encapsulation mechanisms of mRNA within LNPs for vaccine delivery. These new applications exemplify the evolving mission of pharmaceutical sciences: to pose new questions to scientific and technical communities, to enhance collaboration, and to bring back innovative ideas and solutions. This dynamic approach helps drive forward the collective mission of delivering effective drugs to patients.…”
Section: Collaborative Synergy and The Interdisciplinary Nature Of Ph...mentioning
confidence: 99%